Seals, sharks, and social identity: ocean management preferences and priorities - Bratton, Rachel; Dowling-Guyer, Seana; Vaske, Jerry; Jackman, Jennifer (Frontiers in Conservation Science, 2024)
Social identity influences policy preferences and actions regarding wildlife. Using data from a survey of residents, commercial fishers, and tourists on Cape Cod, Massachusetts, this study examined the relationships between self-selected social identities (i.e., animal protection, environmental, hunter, and angler) within these stakeholder groups and ocean management priorities, support for the Marine Mammal Protection Act (MMPA), and acceptance of lethal management of seals and white sharks. Results revealed three social identity clusters: (1) identification with environmental and animal protection groups (non-consumptive), (2) identification with both non-consumptive (environmental, animal protection) and consumptive (angler, hunter) groups, and (3) identification with none of the groups. Residents were a mix of identities; tourists primarily identified with the non-consumptive and, to a lesser extent, no identification clusters; and commercial fishers identified with the mixed non-consumptive/consumptive and no identification clusters. The overlap between consumptive and non-consumptive identifications illustrates the heterogeneity of social identity. Participants in the non-consumptive cluster favored policies prioritizing wildlife, the environment, and marine mammal protections more strongly than those in other clusters. Findings contribute to research examining social identity theory to improve understanding of public wildlife management preferences, within the novel context of rebounding populations of marine predators such as pinnipeds and white sharks.